“Guyub Genre”: Implementation of Meaningful Youth Participation (MYP) by the Forum Generasi Berencana (Genre) Depok City - Johan Arifin; Ida Ruwaida (Jurnal Pendidikan Ilmu Sosial, 2024)
The government encourages the implementation of Meaningful Youth Participation (MYP) in the Program Generasi Berencana (Genre). This study aims to reveal how the MYP principles are understood and implemented by the Depok City Genre Forum through the implementation of “Guyub Genre”. This type of research is qualitative with a single instrumental case study approach. The research results showed that Genre Ambassadors received training on MYP but did not have sufficient understanding. MYP is understood as a basis for activities and the involvement of teenagers as subjects of activities, but there is no clear and binding mechanism for its implementation. “Guyub Genre” as a form of implementing MYP is still limited to proposing ideas to the Regional Development Planning Agency (Bappeda) but is still weak in being involved in decision-making. There is a need to strengthen sufficient capacity for both young people and adults in the bureaucracy, as well as more inclusive mechanisms to strengthen the commitment of young people to participate.